Assessing the Ability of WRF‐BEP + BEM in Reproducing the Wintertime Building Energy Consumption of an Italian Alpine City. Issue 8 (26th April 2021) - Pappaccogli, Gianluca; Giovannini, Lorenzo; Zardi, Dino; Martilli, Alberto
Abstract: This work aims at assessing the ability of the Weather Research and Forecasting model, coupled with a multilayer urban canopy scheme and a building energy model (BEP + BEM), to simulate the building energy consumption in the city of Bolzano (Italy) during wintertime. Estimates of the actual energy consumption, to be adopted as a benchmark for evaluating model results, are obtained from observed total annual values, combined with load curves derived from real‐time measurements in various meteorological conditions and for different building types. The validation of numerical results highlights that the modeling set‐up adopted is able to well reproduce the spatial distribution of the energy consumption in the urban area and its dependence on the morphological characteristics of the city. In particular, it is found that energy consumption in the urban area is particularly influenced by the building height and the building surface area to plan area ratio, highlighting the importance of an accurate representation of the urban morphology in mesoscale meteorological models to obtain reliable estimates of citywide building energy consumption. Moreover, also the diurnal profiles of energy consumption are well captured by the model, especially in the residential area. Larger errors are found in the commercial‐industrial area: here various utilities display peaks of energy demand, that the model cannot reproduce correctly. Key Points: The work aims at assessing the ability of the WRF‐BEP + BEM model to simulate the building energy consumption in the city of Bolzano (Italy) The novelty consists in the direct validation of the simulated consumption for specific climatic conditions across the four urban categories The model well describes both the spatial distribution and the magnitude of the daily average building thermal consumption at city scale